An exploration of the beauty ideals and advertising values represented by cosmetic brands: A case study analysis of Seventeen. - Zhang, Yu-Han (2017)
The literatures of marketing and brand research have paid more and more attention to the values appeared in the advertisements (Gneezy, 2017). What is more, the beauty ideals represented by the advertisements are also a popular research topic in recent years (Gneezy, 2017). However, the development of the beauty ideal and whether the beauty ideal represented by a specific only been explored by a few literatures. In addition to this, whether there is a relationship existing between the beauty ideal and advertising value of a specific brand are also be paid little attention. But individuals accomplish their preferred beauty ideal through paying attention to the recommend make up tips on various media and consuming beauty products (Wolf, 2013). That is to say, cosmetic brands take advantage of the beauty ideal and advertising value to attract their target consumers. Therefore, the advertising value and beauty ideal are crucial for a brand’s development.